2016
DOI: 10.18632/oncotarget.7441
|View full text |Cite
|
Sign up to set email alerts
|

A positive feedback loop involving EGFR/Akt/mTORC1 and IKK/NF-κB regulates head and neck squamous cell carcinoma proliferation

Abstract: The overexpression or mutation of epidermal growth factor receptor (EGFR) has been associated with a number of cancers, including head and neck squamous cell carcinoma (HNSCC). Increasing evidence indicates that both the phosphatidylinositol-3-kinase (PI3K)-Akt-mammalian target of Rapamycin (mTOR) and the nuclear factor-kappa B (NF-κB) are constitutively active and contribute to aggressive HNSCC downstream of EGFR. However, whether these two oncogenic signaling pathways exhibit molecular and functional crossta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 58 publications
4
55
0
Order By: Relevance
“…Nonetheless, a recent report showed that IKK/NF-B activity could be mediated by TSC2 through mTORC1 activation in PTEN-null prostate cancer cells, suggesting that mTORC1 could serve as an upstream modulator for IKK/NF-B activation (54). Another study also reported that mTORC1 activation regulates NF-B activation, which involves upregulation of EGFR and IKK activation, possibly through a positive-feedback loop regulation (55). Feedback mechanisms of downstream events of NF-B activated by LMP1, e.g., EGFR overexpression, may be involved to modulate upstream events, e.g., PI3K/AKT, to induce mTORC1 activation, hence forming a positive-feedback loop in mTORC1/NF-B activation in LMP1-expressing NPC cells to promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a recent report showed that IKK/NF-B activity could be mediated by TSC2 through mTORC1 activation in PTEN-null prostate cancer cells, suggesting that mTORC1 could serve as an upstream modulator for IKK/NF-B activation (54). Another study also reported that mTORC1 activation regulates NF-B activation, which involves upregulation of EGFR and IKK activation, possibly through a positive-feedback loop regulation (55). Feedback mechanisms of downstream events of NF-B activated by LMP1, e.g., EGFR overexpression, may be involved to modulate upstream events, e.g., PI3K/AKT, to induce mTORC1 activation, hence forming a positive-feedback loop in mTORC1/NF-B activation in LMP1-expressing NPC cells to promote tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been described that chemotherapeutic agents stimulate the activation of nuclear transcription factor NF-κB, thus enhancing chemoresistance mechanisms in cancer cells [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Programmed cell death can be suppressed by the nucleus localization of nuclear factor‐ κ B (NF‐ κ B) , which induces the expression of antiapoptotic factors such as the IAPs, the TRAFs, and Bfl‐1 . NF‐ κ B plays a critical role in chemotherapy resistance due to its ability to reduce apoptosis . Apoptotic pathways are related with the sensitivity of target drugs , and Linsitinib resistance in ESCC may be related to apoptosis.…”
Section: Discussionmentioning
confidence: 99%